2018
DOI: 10.3390/nu10020150
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Associations with Metabolic Characteristics in Metabolically Healthy and Unhealthy Adolescents with Severe Obesity: An Observational Study

Abstract: Considering the inadequacy of some antioxidant nutrients in severely obese adolescents, this study aimed to assess the relationship between antioxidant micronutrients status and metabolic syndrome components in metabolically healthy obesity (MHO) and unhealthy obesity (MUO). We performed an observational study in severely obese adolescents (body mass index > 99th percentile) and they were classified into MHO or MUO, according to the criteria adapted for adolescents. Anthropometric, biochemical, and clinical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
(31 reference statements)
2
18
0
4
Order By: Relevance
“…Accordingly, we observed for the first time a negative association between carotenes/TAG and endothelial damage biomarkers aPAI-1 and tPAI-1. Plasma carotenes/TAG were also negatively correlated with insulin and HOMA-IR, which agrees with a previous study that showed serum β-carotene levels to be negatively correlated with glycaemia in adolescents with obesity and MU status [57].…”
Section: Plasma Carotenes/tag Levels Are Decreased In Children With Osupporting
confidence: 92%
“…Accordingly, we observed for the first time a negative association between carotenes/TAG and endothelial damage biomarkers aPAI-1 and tPAI-1. Plasma carotenes/TAG were also negatively correlated with insulin and HOMA-IR, which agrees with a previous study that showed serum β-carotene levels to be negatively correlated with glycaemia in adolescents with obesity and MU status [57].…”
Section: Plasma Carotenes/tag Levels Are Decreased In Children With Osupporting
confidence: 92%
“…Studies analyzing the association between CRP and antioxidant levels in children are scarce and it has been mostly investigated in sick children. The association between CRP and vitamin A, for example, has been analyzed in children with an infectious disease [ 15 ], night blindness [ 16 ] or obesity [ 17 , 18 ]. To our knowledge, no cross-sectional studies analyzing the association of CRP with vitamin levels have been performed in healthy children in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with previous studies which showed that the increase in blood vitamin C concentrations associated with the change in RMR/FFM (43). Garcia and co-workers have shown that low serum concentrations of Vitamin C are correlated with increased body fat and abdominal fat (44). In contrast, some other studies have shown that vitamin C administration signi cantly decreased RMR (45).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, some other studies have shown that vitamin C administration signi cantly decreased RMR (45). A potential mechanism for this correlation could be because of ascorbic acid modulation on lipolysis in the interior of adipocytes and in ammatory response (44). Vitamin C, an antioxidant, regulates glucocorticoid metabolism and gene expression involved in adipogenesis (46).…”
Section: Discussionmentioning
confidence: 97%